2022
DOI: 10.2147/nss.s346984
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea and Risk of Influenza-Associated Severe Acute Respiratory Infection: Real-World Evidence

Abstract: Purpose We executed the presented retrospective cohort study with the purpose of probing the risk of severe acute respiratory infection (SARI) following influenza in patients with sleep apnea. Materials and Methods We executed this real-world study by gathering Taiwan National Health Insurance Research Database (NHIRD) data. From a database containing 1 million individuals sampled at random from the NHIRD, we identified all patients aged 20 years or older with a sleep a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…After multivariate analysis, sleep apnea increased the risk of influenza-associated SARI. 12 Our data, from a nationally representative data set of 25,328 children, lend support to that argument in the pediatric population.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…After multivariate analysis, sleep apnea increased the risk of influenza-associated SARI. 12 Our data, from a nationally representative data set of 25,328 children, lend support to that argument in the pediatric population.…”
Section: Discussionmentioning
confidence: 52%
“…Previous retrospective studies demonstrated the significance of OSA appearing to have higher rates of hospitalization from acute influenza infection in the adult population. 9,11,12 Previous studies have reported that OSA is associated with influenza infection and hospitalization due to influenza in the adult population. Tsai et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are consistent with many other studies demonstrating that OSA appears to be a risk factor for COVID-19 infection or hospitalization [5][6][7][8]10,12,[14][15][16][17]31,32 as for influenza. 33 However, these prior studies utilized hospital records or other databases to identify COVID-19 cases with or without OSA and in some cases were susceptible to collider bias. In contrast, our data are derived from a large general population survey.…”
Section: Discussionmentioning
confidence: 99%